Comparison of different weighing intervals for fitting growth curves of Nellore cattle - Nobre, Paulo Roberto C.; Rosa, Antonio do N.; Silva, Luiz Otávio C. da; Evangelista, Sílvio Roberto M. (Pesquisa Agropecuaria Brasileira, 2014)
From a herd of 2,116 Nellore cattle from the Bonsucesso Ranch, located in Guararapes, SP, Brazil, 955 animals which had been weighted monthly from birth to 24 months of age were selected. This group included male and female progenies, out of six randomly selected sires. Due to significant year and calving season effects on weight (P<0.01), the animals were grouped in to two periods (1963-1970 and 1971-1974) and two calving season (dry season, April-September and rainy season, October-March). Data were classified by sire, sex, period and calving season in 48 subgroups. The weight-age data of each subgroup, for intervals of 1, 2 and 3 months, were fitted to five mathematical models describing growth: Brody, von Bertalanffy, Gompertz, Logistic and Richards. For all models and all weighing intervals the determination coefficients (DC) were greater than or equal to 98.0%. The Brody's DC for intervals of 1 (98.4%), 2 (98.3%). and 3 months (98.4%) were slightly superior to the DC from the other models. According to comparisons on the determination coefficients, regression standard deviations and computational ease there was no difference among the sets of data corresponding to weights taken with intervals of 1, 2 and 3 months.